2006
DOI: 10.1002/xrs.900
|View full text |Cite
|
Sign up to set email alerts
|

Classification of some species, genera and families of plants by x‐ray spectrometry

Abstract: The Linnaean systematic classification of plants has been used for many years but eventually it caused great discord among taxonomists, since it is still based on visual inspection, without the necessary accuracy. Chemical classification methods are also applied, but are destructive and time and reagent consuming, which makes them expensive, and requiring also treatment of the liquid and solid residues. The latter are based on the determination of the proteins in a species that is not encountered in others. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
5

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 11 publications
0
11
0
5
Order By: Relevance
“…The work is going in two directions -either to differentiate the whole patterns, or to find the differences between selected species. The role of XRF in both versions, both WD and ED [29], can be significant. Although the essential idea of using chemistry for establishing species segregation is intuitively based on the differences either in DNA, optionally RNA or on differences in proteins and here the XRF is much useless, the smart use of the method can be very profiting.…”
Section: New and Unique Applicationsmentioning
confidence: 98%
“…The work is going in two directions -either to differentiate the whole patterns, or to find the differences between selected species. The role of XRF in both versions, both WD and ED [29], can be significant. Although the essential idea of using chemistry for establishing species segregation is intuitively based on the differences either in DNA, optionally RNA or on differences in proteins and here the XRF is much useless, the smart use of the method can be very profiting.…”
Section: New and Unique Applicationsmentioning
confidence: 98%
“…Além disso, na Botânica,é possível ver a técnica de XRF sendo utilizada na classificação de algumas espécies, gêneros e famílias de plantas, além da possibilidade de analisar e determinar a presença de cobre e molibdênio em plantas [13][14]. Em outrasáreas, temos exemplos de aplicações em arqueologia sendo utilizada em análises de peças de ouro e em estudo de fluídos mineralizadores em depósitos epitermais [15][16].…”
Section: Xrf E Suas Aplicaçõesunclassified
“…This nondestructive technique showed good results for other types of samples, such as vegetable oils, [16] varnishes [17] and sugar, [18,19] being able to classify them according to a common characteristic or to determine a given variable using multivariate calibration. [20][21][22] The XRSS is based on the analysis of the position of the Raman scattering related to the Rayleigh and Compton ones, according to the chemical environment of the sample. In 1967, Suzuki, [10] working with high spectral resolution and using pure samples of Li, Be, B and C and varying the incidence angle of X-ray source, observed that the positions of Raman and Rayleigh scatterings did not change but a shift in the position of the Compton scattering was observed.…”
Section: Introductionmentioning
confidence: 99%